Impact of heavy metals from electronic waste on bird species concerning biodiversity: A case study in Bellandur lake, Bengaluru, India - Abhishek Kumar; Ravichandran Chandrahasan (Environmental Health Engineering and Management, 2023)
Background: Heavy metals are one of the global environmental challenges from the informal disposal of electronic waste, especially after the post-COVID phase. In the present study, the concentration of three heavy metals (Pb, Cd, and Cr) in the feathers of Corvus splendens, Passer domesticus and roosting sites at Bellandur Lake, Bengaluru, India were analyzed. Methods: A total of nine sediment samples (0-15 cm) were collected from the roosting sites and stored in polyethylene bags, and nine samples of C. splendens and P. domesticus bird shedding feathers through the molting phenomenon were collected naturally to avoid stimuli that can create conflict for the bird. The samples were collected early morning from 5.00 a.m. to 9 a.m. To determine heavy metals (Pb, Cd, and Cr) in feathers and sediments, the samples were digested and subjected to AAS and inductively coupled plasma-mass spectroscopy (ICP-MS). Furthermore, the generalized linear model was analyzed to test the covariance structure of bird diversity. Results: The Pearson’s correlation is found to be significant (P < 0.05) for contaminated sediments and the feathers of the bird. Analysis of variance for the difference in the concentration of heavy metals within the bird’s species feathers was not statistically significant (P < 0.05). Conclusion: The feathers of C. splendens and P. domesticus bird species are associated with blood vessels and heavy metals deposited in the blood through the food chain, which are contaminated with heavy metals. C. Splendens feathers were more contaminated with Cr, Pb, and Cd compared to P. domesticus feathers bird species.